Pengaruh Penambahan Gum Arab Terhadap Pembuatan Plastik Biodegradable dari Air Kelapa - Norma Wahyunita; Ananda Putra; Umar Kalmar Nizar; Fajriah Azra (Jurnal Periodic Jurusan Kimia UNP, 2022)
Plastic is a polymer that we use a lot in everyday life, but it has a bad impact on the environment because it is difficult to degrade in nature. Therefore, a study was carried out to make plastic that is more environmentally friendly, namelyplastic Biodegradable that utilizes bacterial cellulose from Acetobacter xylinum with old coconut water as a medium with the addition of a plasticizer in the form of Polyethylene Glycol (PEG) and the addition of gum arabic additives with variations in the mass of gum arabic, namely 0g , 1g, 3g, 5g and 7g. The bacterial cellulose plastic PEG gum arabic produced was characterized includingwater content, degree ofswelling,testtensile strength, elongation, elasticity, ability biodegradation, functional group analysis (FTIR) and crystallinity test (XRD). The results of testing the water content and degree of swelling on PEG gum arabic bacterial cellulose plastic, obtained plastic with the more mass of gum arabic added, the greater the percentage of water content and degree of swelling. The results of mechanical testing showed an increase in the value of tensile strength and elasticity along with the amount of gum arabic added but the elongation value decreased. In the biodegradation test, it was found that the more gum arabic which was added, the biodegradation ability increased. The analysis of the plastic functional groups showed that there were no new groups formed. Crystallinity analysis showed that the addition of gum arabic can reduce the percentage of crystallinity.